Сердце саламандры: [для детей старшего школьного возраста] / Лене Каабербол - Кобербель Лине (W.I.T.C.H., 2008)
Экземпляры: ф.6 (20161014) / Инвентарный номер: 1982 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: К 12 / ГРНТИ: 17.82.30 / ББК: 84(7Сое)-4